It's 10 o'clock: Do you know where your data are? - Cook, Terry (Technology review (1998), 1995)
For the first time in 3,500 years of archival activity, people produce records that do not exist to the human eye. For the first time, people are not producing, managing, and saving physical artifacts but rather trying to understand and preserve virtual patterns that give the electronic information its content, structure, context, and meaning. Unless organizations adopt a means to control key records and continually migrate them to current software and new storage media, the long-term memory of modern institutions will be in jeopardy. Disaster can occur not only because electronic information is hard to preserve but also because it is hard to control. The key to maintaining critical electronic information lies in being able to determine, sometimes long after the fact, not only the content but also the context of a record in question. A project team of archivists has determined the following set of needs for capturing, maintaining, and using electronic records: 1. Records must be comprehensive. 2. Records must be authentic. 3. Records must be tamper-proof.